The impact of Zr substituted Sr hexaferrite: Investigation on structure, optic and magnetic properties - Almessiere, M.A.; Slimani, Y.; Sertkol, M.; Nawaz, M.; Baykal, A.; Ercan, I. (Results in physics, 2019)
•Zr substituted Sr hexaferrites were prepared without any impurity by sol-gel auto-combustion method.•Optical band gap energy decreased with increasing Zr content.•Zr substituted Sr-hexaferrites exhibit ferrimagnetic nature.•Values of Ms, Mr, and nB decreased with increasing Zr substitution content. Hexaferrite (HFs) of Sr1−xZrxFe12O19 (0.00 ≤ x ≤ 0.10) have been produced through Citrate Sol-gel approach. The characteristic of compositions is studied through XRD (X-ray powder diffractometer), SEM (Scanning electron microscopy), EDX (Energy-dispersive X-ray), TEM (Transmission electron microscopy), DR% (UV–Visible diffuse reflectance spectrophotometer), FT-IR (Fourier transform infrared spectrophotometer). The single-phase Sr hexaferrite was confirmed for each product by XRD. The crystallites size of the products was calculated as 22–40 nm range which makes this material as an appropriate candidate for high density recording media. The optical band gap tends to decrease when increasing the Zr content. The analyses of magnetization versus applied magnetic field, M(H), were performed at room (300 K; RT) and low (10 K) temperatures. The various magnetic parameters including coercivity Hc, squareness ratio (SQR = Mr/Ms), remanence Mr, saturation magnetization Ms and magnetic moment nB were deduced and described in detail. At both considered temperatures, the M(H) results showed ferrimagnetic nature. It is showed that the Zr substitutions significantly affect the magnetizations data. A significant decrease in the Ms, Mr, and nB was observed with Zr substitution.